2015
DOI: 10.1002/jmri.25115
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of the accuracy of MRI to diagnose appendicitis in the general population

Abstract: Purpose To perform a systematic review and meta-analysis of all published studies since 2005 that evaluate the accuracy of MRI for the diagnosis of acute appendicitis in the general population presenting to emergency departments. Materials and Methods All retrospective and prospective studies evaluating the accuracy of MRI to diagnose appendicitis published in English and listed in PubMed, Web of Science, Cinahl Plus, and the Cochrane Library since 2005 were included. Excluded studies were those without an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 43 publications
0
21
1
Order By: Relevance
“…MRI combines the advantages of ultrasound (i.e., it is noninvasive and lacks ionizing radiation) with the high-resolution 3D cross-sectional information of CT [24]. A recent systematic review and meta-analysis of all published studies since 2005 that evaluateed the accuracy of MRI for the diagnosis of acute appendicitis in the general population presenting to emergency departments concluded that MRI has a high sensitivity and specificity for the diagnosis of appendicitis, similar to that reported previously for CT [25]. …”
mentioning
confidence: 62%
“…MRI combines the advantages of ultrasound (i.e., it is noninvasive and lacks ionizing radiation) with the high-resolution 3D cross-sectional information of CT [24]. A recent systematic review and meta-analysis of all published studies since 2005 that evaluateed the accuracy of MRI for the diagnosis of acute appendicitis in the general population presenting to emergency departments concluded that MRI has a high sensitivity and specificity for the diagnosis of appendicitis, similar to that reported previously for CT [25]. …”
mentioning
confidence: 62%
“…In fact, there were only seven occurrences of its use in our study period. This utilization could possibly shift, however, given the number of recent articles highlighting the test accuracy of MRI in this situation (1416). Additionally, our medical center does not have a labor and delivery service; pregnant patients are directed to another local hospital affiliated with our center.…”
Section: Discussionmentioning
confidence: 99%
“…Since the accuracy of ultrasound has been shown to be inferior to CT (10–12), its effect on negative laparotomy rates may be less when compared with CT. For example, a state-level registry study showed that NLR was 9.8% for patients with no imaging, 8.1% for those who had an ultrasound, and 4.5% for those who had a CT (13). Few studies have demonstrated the effect of MRI on NLR, though its accuracy for diagnosing appendicitis has been shown to be similar to CT (1416). One center found that the NLR for pregnant women dropped from 55% to 29% when MRI was introduced into the diagnostic pathway (17).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound has been proposed as one such alternative, but its use is hindered by a relatively high degree of operator dependence, a limitation reflected in the American College of Radiology's Appropriateness Criteria for Right Lower Quadrant Pain, which reserves recommendation for ultrasound to pediatric or pregnant patients . Emerging research has demonstrated encouraging results for the use of magnetic resonance imaging (MRI) to evaluate for appendicitis; two recent systematic reviews and meta‐analyses found pooled sensitivity and specificity of MRI in the evaluation of appendicitis to be ~96% …”
mentioning
confidence: 99%